Determination of the amount of water consumed by various water users of the residential sector - A. G. Zhulin; A. Kh. Aminova; L. V. Belova (Архитектура, строительство, транспорт)
In recent years, the world has seen a decline in the consumption of water by its population. This is due to the increase in the cost of water and the installation of water meters in apartments. Currently, in Russia, the actual water consumption per inhabitant is lower than the established standards. Factors affecting water consumption are up to 15 items, such as the density of residents in the apartment and their position in society.The paper presents the measurement of water consumption in apartments with a different number of inhabitants, looking at the inhabitants of different ages. Deviations from the recommended values for the calculation of internal water supply networks are noted. Based on actual water consumption measurements for various inhabitants, daily water consumption values for various observation periods (day, week, month, year) are given. The average daily rate of water consumption per 1 resident in the apartments under consideration was 74 liters/ per inhabitant/day.